Venom gland size and venom complexity-essential trophic adaptations of venomous predators: A case study using spiders - Pekár, Stano; Bočánek, Ondřej; Michálek, Ondřej; Petráková, Lenka; Haddad, Charles R; Šedo, Ondrej; Zdráhal, Zbyněk (Molecular ecology, 2018)
Specialized predators possess a variety of adaptations. In venomous predators, this may include the size of the venom gland and venom composition. It is expected that due to different foraging strategies, predators with a wide trophic niche (generalists) should possess larger venom glands that contain more diversified components than predators with a narrow niche (specialists). We focused on spiders, as the most diversified group of venomous predators, in which a wide variety of trophic strategies have evolved. We conducted a comparative analysis using 40 spider species, in which we measured the size of their venom gland and venom complexity using proteome profiling methods. The species were classified into three trophic groups: generalists, facultative specialists and obligatory specialists. We found that the venom glands of generalists are larger than those of obligatory specialists, which is presumably due to more frequent prey capture by the former. The complexity of venom of peptides (2-15 kDa) and proteins (15-250 kDa) was more diverse in generalists than in specialists. Multivariate analysis of venom revealed significant differences among the three trophic categories only in the complexity of peptides. Our study thus shows that venom gland size and its content have taken different pathways during the evolution of different trophic strategies in spiders. Generalists evolved larger venom glands with more complex composition, whereas obligatory specialists possess smaller glands with less diverse chemical structures.
Keywords: prey specialization; pavoučí jedy; biologická evoluce; Proteome; proteom; zvířata; Spider Venoms; Biological Evolution; venom gland; specialist; Phylogeny; fylogeneze; Spiders; Araneae; pavouci; generalist; Animals